Apolipoprotein AI and HDL are reduced in stable cirrhotic patients with adrenal insufficiency: a possible role in glucocorticoid deficiency. (March 2014) - Spadaro, Luisa; Noto, Davide; Privitera, Graziella; Tomaselli, Tania; Fede, Giuseppe; Scicali, Roberto; Piro, Salvatore; Fayer, Francesca; Altieri, Ida; Averna, Maurizio; Purrello, Francesco
Abstract Backgrounds and aims: Adrenal insufficiency (AI) has been reported in patients with stable cirrhosis. A lack of substrates has been suggested as a possible contributing pathogenic mechanism leading to glucocorticoid deficiency in these subjects. To better explore this hypothesis, we studied lipoproteins in cirrhotics with and without AI. Methods. A total of 81 cirrhotic patients and 30 normal volunteers were enrolled. The severity of liver disease was graded by Child-Pugh score. Total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglyceride (TG), and apolipoprotein AI (Apo-AI) levels were evaluated. HDL subfractions were measured by gradient gel electrophoresis. Adrenal function was assessed by the Low-Dose Short Synacthen Test. Results. Cirrhotic patients showed a significant reduction of TC, HDL, LDL, TG, and Apo-AI levels compared with controls. HDL3 was significantly lower, while HDL2 was higher, in cirrhotics compared with the controls. AI was observed in 26 patients. TC, TG, HDL, and Apo-AI were significantly reduced in cirrhotics with AI compared with those with normal adrenal function. HDL2 and HDL3 did not differ between these two groups. Delta cortisol was related to TC (r = 0.30, p < 0.01), TG (r = 0.22, p = 0.05), and Apo-AI (r = 0.37, p < 0.001). Multivariate analysis revealed that Apo-AI and HDL were independently associated with AI. Conclusion. Our study shows that TC, TG, HDL, and Apo-AI are reduced in cirrhotics with AI. In particular, because both HDL and Apo-AI play a primary role in providing substrates for steroidogenesis to adrenal cells, this deficiency may contribute to the pathogenesis of AI in these patients.